FAMILY EDUCATION AS ONE OF THE FACTORS OF ECONOMIC SOCIALIZATION OF SENIOR PRESCHOOL CHILDREN - Melnychuk, Tatyana (PSYCHOLOGICAL JOURNAL, 2017)
In conditions of socio-economic transformation contemporary society requires intensive socialization of children since preschool age. In the article analyzed the theoretical approaches in psychology regarding the educational influence of parental family to the socialization of children under senior school age. Has been analyzed and defined the role of parent family as the primary institution of economic socialization of the child that creates a basis of economic awareness and promotes the transformation of the gained knowledge on the adulthood. It was determined that the economic socialization of children is a process of gradual formation of the economic consciousness of the individual in a family environment based on knowledge of the everyday economic reality, examples of parental behavior and their personal values system. Especially the model of parental behavior in the family stands as one of the factors of economic socialization of preschool children and their awareness and perceptions of the dominant features of property and money as systemically factors of economic literacy. The economic education of preschool children involves a focused interaction adult and child, to learning available basic economic concepts, the formation of moral feelings and qualities needed for successful economic activity, the development of interest in the economic sphere of life, the skills of socio-economic behavior. Economic socialization of the child is defined wide sense as a socio-psychological process of entering into the economic system society and was extremely important for both the individual child and for society as a whole. Considered monetary culture as one of the components of the educational process in the family, as the monetary culture of the senior preschool age combines economic knowledge and skills that preschooler implements during economic activity, showing, with economically significant quality and moral values of society. Our research indicates the need for implementing economic education from the preschool age through family education when children receive basic primary experience in the economic relations.